Creation in Crisis Science, Ethics, Theology - Kureethadam, Joshtrom Isaac (Orbis Books, 2014)
Are Christians fulfilling the stewardship commandment of Genesis to care for God's household? When we speak of the "environmental crisis" facing the planet, we reduce the coming catastrophe to a physical problem. In Creation in Crisis, Joshtrom Kureethadam seeks to extend the current understanding of what is truly an ecological crisis to include ethical and spiritual perspectives, arguing that the crisis is not merely an environmental problem, but is truly 'eco-logical' (a discourse about our common home - oikos) in nature. In its careful incorporation of the latest science around issues such as environmental degradation, pollution, climate change, and food production, this book also enters into dialogue with various disciplines in understanding the contemporary ecological crisis. Creation in Crisis offers a depth of vision that yields up profound insights about our present milieu and the future of our common home.